How Can Islamic Banking Thrive in A Dual Banking System? : Legal And Economic Perspectives - Khotib, A Muhyiddin; Siddiqi, Mohamed A (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
The dual banking system in Indonesia, which allows both conventional and Islamic banking to operate side by side, raises fundamental questions about the sustainability and development of Islamic finance. This study explores the challenges and opportunities of Islamic banking in this system by analyzing the legal, regulatory, and economic frameworks that shape its growth. While Islamic banking is supported by Sharia principles, its operational flexibility is often constrained by regulations that align more closely with conventional banking structures. This paper examines the effectiveness of the current legal framework in fostering a level playing field for Islamic banks, evaluates the impact of government policies, and assesses the economic competitiveness of Islamic finance. The findings suggest that regulatory adjustments, increased financial literacy, and stronger institutional support are necessary for Islamic banking to thrive within the dual banking system. The study concludes with recommendations for policymakers to harmonize legal and economic policies to create a more conducive environment for Islamic banking.